2007
DOI: 10.1007/s10745-007-9136-3
|View full text |Cite
|
Sign up to set email alerts
|

One Leg or Two? Food Security and Pastoralism in the Northern Sahel

Abstract: Should pastoralists in dryland Africa diversify or specialize in their productive activities? To investigate this question, we analyze data from a consumption survey and two surveys of the nutritional status of children in addition to qualitative interviews comparing nomadic and sedentary population groups in the Gourma area in northern Mali. We show how the children of pastoralists seem to be better nourished than children of sedentary farmers and that the children of the sedentarized nomads seem to be the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 27 publications
0
37
0
1
Order By: Relevance
“…Comparing the SSR in 1961, 1985, decreasing trends occurred mainly in Northern and Southern Africa (for example, the SSR in South Africa was higher than 1.0 in 1961 and decreased to less than 0.8 in 2007). In 1961, nine countries (Western and Central Africa: Mali, Niger, Chad; Eastern Africa: Rwanda; Southern Africa: Angola, Malawi, Zimbabwe, South Africa and Madagascar) had SSR ratios greater than 1 (Pedersen and Benjaminsen 2008) but, by 2007, only Malawi retained a ratio above 1. Despite the presence of relatively affluent natural resources (Dixon et al 2001b), Southern Africa (i.e., Botswana, South Africa, and Angola, Fig.…”
Section: Ssrmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing the SSR in 1961, 1985, decreasing trends occurred mainly in Northern and Southern Africa (for example, the SSR in South Africa was higher than 1.0 in 1961 and decreased to less than 0.8 in 2007). In 1961, nine countries (Western and Central Africa: Mali, Niger, Chad; Eastern Africa: Rwanda; Southern Africa: Angola, Malawi, Zimbabwe, South Africa and Madagascar) had SSR ratios greater than 1 (Pedersen and Benjaminsen 2008) but, by 2007, only Malawi retained a ratio above 1. Despite the presence of relatively affluent natural resources (Dixon et al 2001b), Southern Africa (i.e., Botswana, South Africa, and Angola, Fig.…”
Section: Ssrmentioning
confidence: 99%
“…The study by Sadler and Magnan (2011) showed that the Northern African region is the largest grain importing region in the world, with severe constraints on arable land and water coupled with a growing population and increasing incomes (Table 2 in Appendix). However, as nomadic 1961, 1985 and 2007 lifestyles are common in Northern Africa, nutrition from stocks and pastoral diet patterns, which are disregarded here, should also be considered (Pedersen and Benjaminsen 2008). The rural semi-arid regions of North Western Africa (i.e., Senegal, Mauritania, Morocco, Algeria, and Tunisia) also suffered from low SSR during the study period (Fig.…”
Section: Ssrmentioning
confidence: 99%
“…The region is often considered to be particularly vulnerable to climate change and human activities (1,2). Herders and farmers in the Sahel have long recognized the importance of short-term rainfall variability on farm and livestock production, with drought being the principal cause of food insecurity (3). Rainfall largely controls net primary productivity (NPP), forage availability, and livestock carrying capacity (1), and is a primary driver of carbon cycling (4,5).…”
mentioning
confidence: 99%
“…Pastoralism is a form of animal husbandry especially adapted to marginal and unstable grazing resources (Pedersen and Benjaminsen 2008); it is a system based on extensive land use and often involves moving the herds between pastures as a way of coping with spatial and time variations in the grazing conditions in search of fresh pasture (Niamir-Fuller 2000, Dong et al 2011. Sámi reindeer husbandry is a type pastoralism.…”
Section: Contextualizing the Studymentioning
confidence: 99%